Modeling the RF heating uniformity contributed by a rotating turntable. (February 2023) - Wang, Lu; Kang, Jiayi; Zhu, Chenglong; Zhou, Zhongxiang; Wang, Shaojin; Huang, Zhi
Abstract: To explore the potential of using an angle-adjustable rotating device to improve the radio frequency (RF) heating uniformity of packaged food powder, a 3-D mathematical model was established using moving domain approach to predict effects of different rotation directions, speeds and package dimensions on temperature uniformity of red pepper powder (RPP) in a cylindrical container heated in a 6 kW, 27.12 MHz parallel plate RF system. The calculated end point temperatures from the model were in good agreement with those of the experiment at nine locations inside the sample, with a smallest maximum temperature difference of 3.26 °C at all 9 locations. Temperature distributions on the upper, middle and bottom surfaces and the central vertical section of RPP measured by an infrared camera were also matched well with the simulation results, which validated the mathematical model. Experimental and simulation results both showed that a best heating uniformity of RPP could be obtained with an inclined angle of 20° and rotation speed of 4 rad min −1 when RF heating to the pasteurizing temperature of 70 °C. The heating uniformity index (UI) decreased from 0.41 to 0.25 and the maximum temperature of packaged RPP was reduced from 105 °C to 88.7 °C, comparing with an inclined angle of 0° and rotation speed of 0 rad min −1 . With the combined inclined angle and rotational movement of sample, the reduced temperature gradients showed that the heating uniformity was improved volumetrically. Therefore, the laboratory-scale rotating device could lay a substantial foundation for its large-scale applications in RF systems and make food products to reach the target temperature more controllable. Highlights: Sample rotation was proposed as a novel strategy to improve the RF heating uniformity. Temperature increases at edges and corners were limited by the combined inclined angle and rotational movement of sample. The strategy reduces the temperature gradient and improves the heating rate and efficiency.